The Exclusiveness of Political Parties and Growing Corruption in Indonesia’s Democracy - Irham, Muhammad Aqil (Masyarakat: Jurnal Sosiologi, 2020)
"The most common definition of corruption is the abuse of public office for private gains. This definition is well formulated by Klitgaard in his elegant equation: Corruption=Monopoly+Discretion– Accountability. In order to improve this formula and make it fit with Indonesian context, Sujatmiko modified it to: Corruption=Monopoly+Discretion– Accountability–Social Control. The addition of ‘Social Control’ to this formula provides a sociological ground into the theoretical approach to corruption. However, the resulted formula still relies on ‘office-based definition of corruption’—a definition that, according to Warren, fits well in the context of administration and bureaucracy, but inadequate to properly understand corruption in a political context. In the case of Indonesian politics, a more ‘political definition’ of corruption is needed, since the emergence of political party as a strong democratic institution provides a fertile domain for corruption to proliferate. Warren’s ‘democratic conception of corruption’ has given a way for this kind of definition. However, in the context of practical politics in post-Soeharto Indonesia’s direct electoral and multiparty system, Warren’s framework needs to be contextualized by examining how the ‘real politics’ works, especially in inter-actors relations centering on political parties’ crucial role in gaining and distributing political power. In this regard, this article shows how the exclusiveness of political parties encourages the proliferation of politically corrupted practices among political actors in Indonesia.